Whole genome sequencing and molecular detection of potato virus X in Bangladesh - Md. Shafiqul Islam; Md. Akash Ahammed; Fahmida Akhter; Mosaddiqur Rahman; Md. Mosharraf Hossain Molla (PLoS ONE, 2025)
Potato Virus X (PVX) is a significant viral pathogen affecting potato (Solanum tuberosum) crops globally, yet its molecular characterization in Bangladesh remains limited. This study presents the first whole genome sequence (WGS) and molecular analysis of PVX isolated from potato plants in Gazipur, Bangladesh. Initial virus detection was performed using DAS-ELISA on symptomatic potato leaves, followed by RT-PCR targeting the coat protein (CP) gene, which confirmed PVX presence in ‘Patnai’ and ‘Challisha’ potato varieties through a 562 bp amplicon. The WGS of the Patnai-PVX isolate was determined to be 6,435 nucleotides long and deposited in GenBank (accession: PQ527059). Genome analysis identified five major open reading frames encoding the RNA-dependent RNA polymerase (RdRp), triple gene block proteins (TGBp1, TGBp2, TGBp3), and CP. Basic Local Alignment Search Tool X (BLASTX) analysis revealed high sequence similarity with PVX isolates from neighboring regions, suggesting evolutionary conservation. Mutation analysis identified 265 SNPs, predominantly synonymous mutations, indicating maintained protein-coding integrity despite genetic variation. Fewer non-synonymous mutations were detected, potentially affecting viral protein functions and pathogenicity. Phylogenetic analysis based on the entire genome sequence placed the Bangladeshi isolate (PQ527059.1) in a well-supported clade (bootstrap value 99%) with isolates from Peru (MT752634.1, MT752612.1, MT752621.1), highlighting potential international transmission routes while also exhibiting unique genetic markers indicative of regional specificity. This comprehensive molecular characterization enhances understanding of PVX genetic diversity and evolution in Bangladesh, providing valuable insights for developing effective virus management strategies in potato cultivation.